"Today Is So Cool Nobody Wants to Leave": What Makes Teenagers Engaged in Developing Educational Games at School? - de Morais, Dyego Carlos Sales; Falcão, Taciana Pontual (Anais do Simpósio Brasileiro de Informática na Educação (SBIE); 2017: Anais do XXVIII Simpósio Brasileiro de Informática na EducaçãoDO - 10.5753/cbie.sbie.2017.807, 2017)
The current generation of young learners demands innovative educational approaches that meet their characteristics and needs. Recent initiatives go beyond the use of games and propose that students can construct games themselves, developing design and programming abilities, and learning curricular contents in more engaging ways. However, integrating digital games to formal educational settings involves several aspects related to the structure of educational systems and traditional methods of teaching. This research analyzes two school-based processes of game development and identifies aspects that promote student engagement. Results form the basis for modeling a process for game development in the educational context.